Isolation of Gram-negative bacilli and Staphylococci, after two handwashing techniques, in Nursing students who perform hospital practices - Orellana Guevara, Raquel (2019)
Objective: The purpose of the research was the isolation of microorganisms of the genusStaphylococcus and Bacillus Gram negative after two handwashing techniques, during the laboratorypractices of nursing students. Methodology: The research was correlational and transversal, carriedout in May 2018; The participants were 40 students distributed in two groups (Control and experimentalgroups). Samples were taken by swab from recently washed hands. The 11-step clinical handwashing(CML) was applied in the control group and the 3-cycle CML in the experimental group, after training.Isolation, identification and microbial count was carried out in suitable and selective culture media.The data was processed in the Excel program, using tests of statistical significance and descriptivestatistics. Results: Negative Staphylococcus cuagulase was isolated in 40% of the total participants; Depending on the type of washing this microorganism was found in 50% of participants who appliedthe 11-step CML, and in 30% of participants after the 3-stroke CML. Regarding the search for Gramnegativebacilli, Klebsiella spp was found in 5% of the total participants in the 3-stroke CML. Bacterialcounts were lower in the 3-stroke CML and a statistically significant difference of p = 0.033 (p≤0.05) wasobtained when comparing both washing techniques. Conclusions: There was a difference betweenthe two handwashing techniques in bacterial counts, with greater growth after the 11-step CML, andlower growth in the 3-stroke CML. The most frequent microorganism was Staphylococcus cuagulasenegative and in a minimum of samples, Klebsiella spp.